The path to COVIS: A review of acoustic imaging of hydrothermal flow regimes. (November 2015) - Bemis, Karen G.; Silver, Deborah; Xu, Guangyu; Light, Russ; Jackson, Darrell; Jones, Christopher; Ozer, Sedat; Liu, Li
Abstract: Acoustic imaging of hydrothermal flow regimes started with the incidental recognition of a plume on a routine sonar scan for obstacles in the path of the human-occupied submersible ALVIN. Developments in sonar engineering, acoustic data processing and scientific visualization have been combined to develop technology which can effectively capture the behavior of focused and diffuse hydrothermal discharge. This paper traces the development of these acoustic imaging techniques for hydrothermal flow regimes from their conception through to the development of the Cabled Observatory Vent Imaging Sonar (COVIS). COVIS has monitored such flow eight times a day for several years. Successful acoustic techniques for estimating plume entrainment, bending, vertical rise, volume flux, and heat flux are presented as is the state-of-the-art in diffuse flow detection.